Pengembangan Kreativitas Anak Usia Dini Melalui Pemanfaatan Teknologi Digital di PAUD - Dwi Nomi Pura; Tri Imanda Aulia; Sintia Olivia; Mela Oktavia (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The development of digital technology has created many opportunities in the field of education, including early childhood education. The use of digital technology in learning can be an alternative way to support the development of children's creativity. This study aims to examine how digital technology can be utilized to develop creativity in early childhood education. This research uses a descriptive approach with a literature study method by reviewing various sources such as journals, books, and previous studies related to the topic. The results of the study show that the use of digital technology, such as interactive learning applications, educational videos, and other digital media, can provide more engaging and varied learning experiences for children. Through these media, children are able to express ideas, develop imagination, and participate in creative activities during the learning process. However, the use of digital technology still requires guidance from teachers so that it can be used appropriately according to learning objectives and children's developmental needs. Therefore, digital technology can be an effective learning medium to support the development of creativity in early childhood education..